Analysis of Inter-Industry Relations in Pakistan for 1975 -76 (The Pakistan Development Review, 1985)
Input-Output tables provide a detailed accounting of the goods and services that individual industries buy from and sell to each other, and , therefore, constitute a useful medium for an analysis of the interdependent nature of the various sectors of an economy. The PIDE's release of input-output (I-D) tables of Pakistan's economy for the year 1975 -76 [9] is an important contribution in this respect. An 'open' output determination of model of the Leontief type is applied to the said data base to delineate the structural interdependence of Pakistan's economy. Some salient features of the economy such as sectoral distribution of the value added, cost composition of the value of sectoral outputs, output and income multipliers are discussed in Section l. The notion of interdependence arising through technological interconnections between various sectors implies structural linkages - both “backward” and “forward”. Quantification of these linkages provides an effective way of identifying "key sectors" of the economy. Section II discusses the methodology used and the empirical results obtained pertaining to key sectors of the Pakistan's economy. Some concluding remarks are offered in Section Ill.